Toxicity of glyphosate accelerates neurodegeneration in Caenorhabditis elegans model of Alzheimer’s disease - Rani, Nisha; Alam, Mohammad Mumtaz; Parvez, Suhel (Frontiers in Toxicology, 2025)
IntroductionPesticide-related environmental contamination poses a growing global concern, threatening human health, wildlife, and ecosystems. Glyphosate (N-phosphonomethyl-glycine, GLY), a widely used organophosphorus herbicide, has been associated with neurotoxic effects. This study investigates the potential neurodegenerative impact of glyphosate using a Caenorhabditis elegans Alzheimer’s disease (AD) model.MethodsTransgenic C. elegans strain CL4176, which expresses human amyloid-beta (Aβ1–42) upon temperature induction, was exposed to various concentrations of glyphosate (12, 15, 18.5, 20, and 25 mg/L) for 24 hours. Behavioral assays (body bends, head thrashes, body length, and pharyngeal pumping), oxidative stress markers (catalase activity), and Aβ protein expression were evaluated.ResultsGlyphosate exposure induced a concentration-dependent decline in locomotor and feeding behaviors. Catalase activity was significantly reduced, indicating elevated oxidative stress. Additionally, a marked increase in Aβ1‐42 protein expression was observed in glyphosate-treated CL4176 worms.DiscussionThese findings suggest that glyphosate exacerbates Aβ toxicity and induces AD-like phenotypes in the C. elegans model through behavioral impairment, oxidative stress, and increased Aβ accumulation. Glyphosate’s potential contribution to neurodegenerative processes warrants further investigation.